Quality of Counter-Terrorism Services in Poso District Central Sulawesi Province - Abdullah, Fitriani; Hanafi, Imam (Journal of Public Administration and Government, 2024)
The purpose of the study is to provide an overview of terrorism prevention and coping policies in Poso Province, Central Sulawesi. The method used in this study was qualitative research method to obtain more accurate data according to the research objectives, and five informants were also selected using the objective informant selection method. The theory used as a knife of analysis by Daryanto and Setyobudi (2014) on service quality consists of the indicators of Attitide, Attention, Action, and Anticipation. The results of the study explained that the quality of terrorism management services in Poso Province, Central Sulawesi is not operating optimally because of the aspects of the four locally tested aspects that are not performing well, namely the justice aspect. From this data, it can be concluded that the implementation of Quality of Terrorism Services in Poso Province, Central Sulawesi is not operating optimally because three of the aspects are working well, but one aspect is not working well.